Dam foundation failure analysis. Discontinuum models and rock mass parameters - Lemos, J. V. (2012)
Identification of potential failure mechanisms defined by the rock mass discontinuities or the concrete-rock interface plays an important role in the safety assessment of concrete dam foundations. The paper presents instances of application of discrete elements deformable block models for analysis of these failure scenarios, representing the rock mass foundation and the concrete dam. The rock mass characterization needs and the methodologies for obtaining the input parameters for these models are discussed.